Maternity health care professionals' views and experiences of fetal genomic uncertainty: A review. (20th April 2020) - Hui, Lisa; Szepe, Emma; Halliday, Jane; Lewis, Celine
Abstract: The field of prenatal screening and diagnosis for fetal anomalies has been marked by a rapid succession of technological advances, including most notably, chromosomal microarray analysis, and next generation sequencing. Despite the diagnostic advantages of these technologies, their incorporation into prenatal testing has created additional challenges of revealing genomic variants of unknown or uncertain significance, and secondary findings. While detailed posttest counseling about uncertain variants is best performed by medical geneticists, many of the screening and diagnostic tests that lead to this information are actually ordered by general maternity health care professionals (HCPs), such as obstetricians, midwives, and family physicians. Maternity HCPs support pregnant women through to the conclusion of their pregnancy and the postpartum period, and thus are close observers of the psychosocial impart of fetal genomic uncertainty on women and their families. While there have been many studies exploring the handling of genomic uncertainty by genetics HCPs, there has been relatively less attention paid to maternity HCPs without speciality training in genetics. This review explores the current literature surrounding nongenetic maternity HCPs' views and experiences of genomic uncertainty and returning uncertain results in the prenatal setting.